Pengoperasian Penyimpan Energi Udara Tekan Skala Kecil Mode Discharged pada Efisiensi Maksimum - Andi Setiawan; Ardyono Priyadi; Mauridhi Hery Purnomo (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2019)
This paper presents the results of research on the development of small-scale compressed air storage operating at its maximum efficiency. In contrast to what was done in previous studies using a buck converter on the output side of the generator, here a boost converter is used. The use of a boost converter allows the turbines to operate at a reasonably low speed and can still produce the desired voltage for the load, which is 12 volts. This strategy is chosen based on the characteristics of the turbine which indicates that the turbine will operate with better efficiency if operated at lower speeds. In this study, the search for maximum efficiency points is done by perturb and observe (P&O) method. The simulation results show that this strategy is effective for obtaining operating points with maximum efficiency if the load power is small relative to the nominal power of the turbine-generator, which is below 50%.